Instructional Leadership, Teacher Commitment, and Motivation as Predictors of Holistic Child Development in TABIKA KEMAS - Nor Maizatul Akmal Mohd Zubir; Mazni Muhammad; Adi Bandono (Universitas Negeri Padang, 2026)
This study examines the influence of instructional leadership, teacher commitment, and teacher motivation on the holistic development of TABIKA KEMAS children in Northern Malaysia. A quantitative survey design was employed involving 313 TABIKA KEMAS teachers from Kedah, Perak, and Penang. Data were analysed using SPSS through descriptive statistics, Pearson correlation, and multiple regression analyses. The findings revealed that instructional leadership (M = 4.04), teacher commitment (M = 4.10), teacher motivation (M = 3.84), and holistic child development (M = 3.81) were all at high levels. Pearson correlation analysis indicated that teacher motivation had a strong and significant positive relationship with holistic child development (r = 0.694, p < .001), whereas instructional leadership showed no significant relationship. Multiple regression analysis further demonstrated that teacher motivation was the strongest predictor of holistic child development (β = 0.835, p < .001), explaining 81.7% of the total variance (R² = 0.817). The findings highlight the importance of strengthening teacher motivation in improving preschool educational quality and enhancing children’s holistic developmental outcomes within TABIKA KEMAS institutions.